Influence of the Umbilical Cord Insertion Site on the Optimal Individual Birth Weight Achievement. (25th May 2014) - Brouillet, Sophie; Dufour, Anaïs; Prot, Fabien; Feige, Jean-Jacques; Equy, Véronique; Alfaidy, Nadia; Gillois, Pierre; Hoffmann, Pascale
Abstract : Study Question . To determine whether the umbilical cord insertion site of singleton pregnancies could be linked to the newborn birth weight at term and its individual growth potential achievement. Material and Methods . A cohort study including 528 records of term neonates was performed. Each neonate was assessed for growth adjusted for gestational age according to the infant's growth potential using the AUDIPOG module. We considered two categories of umbilical cord insertions: central and peripheral. Intrauterine growth restriction was defined as birth weight below the 10th percentile. Statistical analysis was performed using Chi-square, Student's t test, Wilcoxon test, ANOVA, and logistic regression. Results . We observed a total of 343 centrally inserted cords versus 185 peripheral cords. There were twice as many smokers in the mothers of the peripheral category compared to the centrally inserted ones. More importantly, we demonstrated that only 17/343 (5.0%) of infants with central cord insertion were growth restricted, compared to 37/185 (20.0%) of the infants born with a peripheral insertion. Neonates with centrally inserted cord were significantly heavier. Conclusion . The umbilical cord insertion site of singleton pregnancies is associated with the newborn's birth weight at term and its individual growth potential achievement.